2007
DOI: 10.1007/s11117-007-2084-8
|View full text |Cite
|
Sign up to set email alerts
|

Ideals of Multilinear Forms – a Limit Order Approach

Abstract: A general theory of limit orders for ideals of multilinear forms is developed. We relate the limit order of an ideal to those of its maximal hull and its adjoint ideal. We study the limit orders of the ideals of dominated and multiple summing multilinear forms. Finally, estimates of the diagonal of a (non-necessarily diagonal) multilinear form are presented, in terms of the limit order of the ideals to which it belongs.2000 Mathematics Subject Classification:46G25, 46A45

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Proof. As in the proof of [9,Theorem 3.5] we can see that, if M is a finite dimensional space, then (D n r ) * (M ) = I n r (M ). Let p ∈ {1, 2, ∞}, we have that gl I n r (ℓ m p ) = gl D n r (ℓ m p ) , which we already know by the previous example that this goes to ∞ with m.…”
Section: Unconditionality In Ideals Of Polynomials and Multilinear Formsmentioning
confidence: 67%
See 1 more Smart Citation
“…Proof. As in the proof of [9,Theorem 3.5] we can see that, if M is a finite dimensional space, then (D n r ) * (M ) = I n r (M ). Let p ∈ {1, 2, ∞}, we have that gl I n r (ℓ m p ) = gl D n r (ℓ m p ) , which we already know by the previous example that this goes to ∞ with m.…”
Section: Unconditionality In Ideals Of Polynomials and Multilinear Formsmentioning
confidence: 67%
“…If T is any multilinear form on ℓ p , we denote by D(T ) the multilinear form obtained from T setting to zero all the coefficients outside the diagonal (see [9] for details).…”
Section: ])mentioning
confidence: 99%
“…In [5] it is shown that the ideal of r-dominated n-linear forms is maximal and a finitely generated n-tensor norm is presented to which it is dual. Using the same ideas we prove an analogous statement for vector-valued polynomials.…”
Section: Relation With Tensor Normsmentioning
confidence: 99%
“…Matos' research report [1] are usually quoted as the precursors of the now well-known nonlinear theory of absolutely summing operators. In the last decade this topic of investigation attracted the attention of many authors and various different concepts related to summability of nonlinear operators were introduced; this line of research, besides its intrinsic interests, highlighted abstract questions in the mainstream of the theory of multi-ideals which contributed to the revitalization of the general interest in questions related to ideals of polynomials and multilinear operators (see [9,10,15,27,28]). This paper has a twofold purpose: to summarize/organize some information constructed in the last years concerning the different multilinear generalizations of absolutely summing operators; and to sketch a research project directed to the investigation of the existence of multilinear ideals (related to the ideal of absolutely summing operators) satisfying a list of properties which we consider natural.…”
Section: Introductionmentioning
confidence: 99%
“…Matos' research report [1] are usually quoted as the precursors of the now well-known nonlinear theory of absolutely summing operators. In the last decade this topic of investigation attracted the attention of many authors and various different concepts related to summability of nonlinear operators were introduced; this line of research, besides its intrinsic interests, highlighted abstract questions in the mainstream of the theory of multi-ideals which contributed to the revitalization of the general interest in questions related to ideals of polynomials and multilinear operators (see [9,10,15,27,28]).…”
Section: Introductionmentioning
confidence: 99%